Nonreversible MAIT cell‐dysfunction in chronic hepatitis C virus infection despite successful interferon‐free therapy. Issue 9 (12th July 2016) - Hengst, Julia; Strunz, Benedikt; Deterding, Katja; Ljunggren, Hans‐Gustaf; Leeansyah, Edwin; Manns, Michael P.; Cornberg, Markus; Sandberg, Johan K.; Wedemeyer, Heiner; Björkström, Niklas K.
Abstract : Loss of peripheral blood MAIT cells represents a major immunological phenotype in patients with chronic HCV‐infection. Residual MAIT cells were highly activated and exhibited suppressed responsiveness after E. coli stimulation. The observed phenotype was not reinvigorated after successful HCV‐clearance using interferon‐free therapy. Abstract : Immune exhaustion is a hallmark of chronic viral infections. However, pathogen eradication can result in reinvigorated immune responses. Indeed, this was recently suggested for antigen‐specific CD8 + T cells and NK cells in HCV‐infected patients receiving an interferon‐free treatment regimen. Mucosal‐associated invariant T (MAIT) cells are evolutionarily conserved innate‐like effector T cells. Here, we show that MAIT cells are severely diminished in frequency in chronic HCV‐infection, and in this regard the most affected immune cell type in peripheral blood of humans with this disease. Residual MAIT cells show an activated phenotype with high expression of granzyme B, HLA‐DR, PD‐1, and CD69 as well as altered transcription factor expression and suppressed responsiveness to MR1‐dependent antigen stimulation. In contrast to other immune cells, MAIT cells are not reinvigorated after successful HCV‐clearance using interferon‐free therapy. The present results hence demonstrate persistent immune cell‐dysfunction in humans despite successful elimination of a chronic pathogen.